Предмет: Математика,
автор: malanchenko2285a
2(0,2х-3)-8(0,7х-4)=39
Ответы
Автор ответа:
10
Ответ:
2(0,2х - 3) - 8(0,7х - 4) = 39
раскрываем скобки
0,4х - 6 - 5,6х + 32 = 39
-5,2х + 26 = 39
-5,2х = 39 - 26
-5,2х = 13
х = -2.5
Ответ: -2,5
Автор ответа:
2
Ответ:
0,4х - 6 - 5.6х + 32 = 39
-5.2х + 26 = 39
-5.2х = 13
х = 13/-5.2
х = -2.5
Ответ: -2.5
Пошаговое объяснение:
Похожие вопросы
Предмет: Литература,
автор: LexUp
Предмет: Химия,
автор: Яна1526
Предмет: Русский язык,
автор: юландия
Предмет: Математика,
автор: Trabl311
Предмет: Математика,
автор: алуа30